Reindeer Anthrax in the Russian Arctic, 2016: Climatic Determinants of the Outbreak and Vaccination Effectiveness - Liskova, Elena A.; Egorova, Irina Y.; Selyaninov, Yuri O.; Razheva, Irina V.; Gladkova, Nadezhda A.; Toropova, Nadezhda N.; Zakharova, Olga I.; Burova, Olga A.; Surkova, Galina V.; Malkhazova, Svetlana M.; Korennoy, Fedor I.; Iashin, Ivan V.; et al. (Frontiers in Veterinary Science, 2021)
Yamal Peninsula (Russian Federation) experienced a massive outbreak of anthrax in reindeer (Rangifer tarandus) in July–August 2016, with 2,650 (6.46% of total susceptible population) animals infected, of which 2,350 died (case fatality rate of 88.67%). In our study, we analyzed climatic and epidemiological factors that could have triggered the outbreak. The cancellation of reindeer vaccination against anthrax in 2007 resulted in an increase in population susceptibility. In response to the outbreak, total vaccination of all susceptible animals was resumed. To assess the vaccination effectiveness, we tested 913 samples of blood serum taken from vaccinated reindeer using an antigenic erythrocyte diagnostic kit to detect specific anti-anthrax antibodies by indirect hemagglutination assay (IHA) 9 months after vaccination. We found that 814 samples had a sufficiently high level of anti-anthrax antibodies to indicate a protection level of 89% (95% CI: 87%‒91%) of the whole reindeer population. Abnormally high ambient temperature in the summer of 2016 contributed to the thawing of permafrost and the reactivation of soil reservoirs of Bacillus anthracis; the monthly average air temperature in June 2016 and July 2016 were 25% and 100% higher than in previous years, respectively, while the maximum air temperatures were 14% and 35% higher. Using the projected climate data for 2081–2100 according to the “worst case” RCP8.5 scenario, we demonstrated that the yearly air temperature may average above 0℃ across the entire Yamal Peninsula, while the yearly number of days with a mean temperature above 0°С may rise by 49 ± 6 days, which would provide conditions for reactivation of soil anthrax reservoirs. Our results confirmed the climatic conditionality of anthrax, underlined the importance of vaccination for controlling the epidemic process, and demonstrated the effectiveness of monitoring studies using the IHA diagnostic kit for detecting erythrocyte anthrax antigens.